Restitution: A New Paradigm for Criminal Justice - Barnett, Randy E (1977)
This paper will analyze the breakdown of our system of criminal justice in terms of what Thomas Kuhn would describe as a crisis of an old paradigm- punishment. I propose that this crisis could be solved by the adoption of a new paradigm of criminal justice-restitution. The approach will be mainly theoretical, though at various points in the discussion the practical implications of the rival paradigms will also be considered. A fundamental contention will be that many, if not most, of our system's ills stem from errors in the underlying paradigm. Any attempt to correct these symptomatic debilities without a reexamination of the theoretical underpinnings is doomed to frustration and failure. Kuhn's theories deal with the problems of science. What made his proposal so startling was its attempt to analogize scientific development to social and political development. Here, I will simply reverse the process by applying Kuhn's framework of scientific change to social, or in this case, legal development